Islamic Educational Values in Inclusive Learning Practices: A Case Study at a Primary School in Yogyakarta - Salsabilla, Nulqia; Suprihatiningrum, Jamil; Musyakkir, Musyakkir; Raudhatunnur, Raudhatunnur (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2025)
Islamic education, with its emphasis on moral and spiritual values, offers a strong foundation for fostering an inclusive learning environment. This study aims to examine the integration of Islamic values within inclusive learning practices at a primary school and to identify the challenges encountered in their implementation. Employing a qualitative approach and a case study design, the research involved in-depth interviews with special education teachers (GPK) and direct classroom observations. The findings reveal that Islamic values—such as justice, compassion, equality, and tolerance—are effectively applied in the school's inclusive practices. Nevertheless, the implementation faces notable challenges, including a shortage of GPK personnel and limited parental acceptance of children with special needs. Despite these obstacles, the school continues to make concerted efforts to ensure that every student feels welcomed and valued. The study concludes that Islamic values play a vital role in supporting inclusive education by fostering a just, compassionate, and equitable environment that promotes both social and academic development. Abstrak: Pendidikan Islam dengan nilai-nilai moral dan spiritualnya dapat memberikan landasan yang kuat untuk menciptakan lingkungan pembelajaran yang inklusif. Penelitian ini bertujuan untuk mengeksplorasi penerapan nilai-nilai Islam dalam praktik pembelajaran inklusif di sekolah dasar dan mengidentifikasi tantangan yang dihadapi dalam implementasinya. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus, yang melibatkan wawancara mendalam dengan guru pendamping khusus (GPK) dan observasi langsung. Hasil penelitian menunjukkan bahwa meskipun nilai-nilai Islam seperti keadilan, kasih sayang, kesetaraan dan toleransi telah diterapkan dengan baik, masih terdapat tantangan signifikan seperti keterbatasan jumlah GPK dan rasa keberterimaan orang tua terhadap anak mereka yang berkebutuhan khusus. Namun, upaya untuk memastikan setiap siswa merasa diterima dan dihargai terus dilakukan oleh pihak sekolah. Penelitian ini mengindikasikan bahwa nilai-nilai Islam seperti keadilan, kasih sayang, kesetaraan, dan toleransi, mendukung implementasi pendidikan inklusif yang dapat menciptakan lingkungan yang adil dan mendukung perkembangan sosial serta akademik siswa.